2019
DOI: 10.1039/c9an90016k
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Solution-processed wrinkled electrodes enable the development of stretchable electrochemical biosensors

Abstract: Correction for 'Solution-processed wrinkled electrodes enable the development of stretchable electrochemical biosensors' by Yuting Chan et al., Analyst, 2019, 144, 172-179. The authors regret that an incorrect unit was stated in the abstract and conclusion of the original article. The sensitivity was given as 750-810 μA M −1 cm −2 . The correct value should be 750-810 μA mM −1 cm −2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[141] Wrinkling of gold electrodes has been widely adopted into biosensing strategies from nucleic acid detection [140,142] to wearable sensors for detection of biomarkers in biological fluids. [143,144] These nanostructured materials have also been applied to microbial fuel cells. [145] It has been demonstrated that wrinkled gold with tall and largely spaced features allows for better bacterial packing and therefore amplified signal generation.…”
Section: Wrinkled Noble Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[141] Wrinkling of gold electrodes has been widely adopted into biosensing strategies from nucleic acid detection [140,142] to wearable sensors for detection of biomarkers in biological fluids. [143,144] These nanostructured materials have also been applied to microbial fuel cells. [145] It has been demonstrated that wrinkled gold with tall and largely spaced features allows for better bacterial packing and therefore amplified signal generation.…”
Section: Wrinkled Noble Metalsmentioning
confidence: 99%
“…The random orientation of wrinkles can aid immensely with mitigating tensile stress on the electrode, and complete recovery of conductivity after repeated straining has been reported . Wrinkling of gold electrodes has been widely adopted into biosensing strategies from nucleic acid detection to wearable sensors for detection of biomarkers in biological fluids . These nanostructured materials have also been applied to microbial fuel cells .…”
Section: Noble Metals In Diagnostics and Biomedicinementioning
confidence: 99%